2018
DOI: 10.1159/000487929
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight and Obesity in Hungarian Children and Adolescents

Abstract: Background/Aims: The prevalence of overweight and obesity in children and adolescents is increasing worldwide, and this condition is a risk factor for cardiovascular mortality. The aim of this study was to assess the prevalence of overweight and obesity among the 3–18-year-old population in Szolnok City and the surrounding areas. Methods: Anthropometric data from healthy, white individuals recruited from nursery, elementary, and secondary schools were used to assess the prevalence of obesity and overweight in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Children with excessive weight had abnormal BP and HTN significantly more often than proportional ones [3,5,6,22,23,30], but we did not identify statistically better sensitivity of AAP criteria by reclassification, which may be due to an insufficient number of identified patients. However, an Italian study with analysed a sample 2929 overweight/obese young people (6-16 years old) identified that children considered non-hypertensive by ESH 327 (11%) were reclassified using the lower cut-off point suggested by the AAP [7].…”
Section: Discussioncontrasting
confidence: 77%
“…Children with excessive weight had abnormal BP and HTN significantly more often than proportional ones [3,5,6,22,23,30], but we did not identify statistically better sensitivity of AAP criteria by reclassification, which may be due to an insufficient number of identified patients. However, an Italian study with analysed a sample 2929 overweight/obese young people (6-16 years old) identified that children considered non-hypertensive by ESH 327 (11%) were reclassified using the lower cut-off point suggested by the AAP [7].…”
Section: Discussioncontrasting
confidence: 77%
“…A recent nationwide population-based study showed that the prevalence of T2DM among children and adolescents in Hungary was 22 out of 100,000 [33] and this data was higher than in most European countries (such as Denmark [34] and Germany [35]). The prevalence of obesity among children or adolescents was 6.6% [36], while among adults (above 18 years) it was 32% [37]. Hungary has the highest obesity rate in Europe based on OECD data from 2016 [38].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, despite the number of studies that have been performed, the prevalence of high BP values in pediatric population worldwide is difficult to establish partly due to regional differences in the definition, distribution of reference BP data and methods of BP measurement. Central-European studies showed the prevalence of high BP values in adolescents from as low as 2.2% in Switzerland to 4.9% in Poland ( 22 - 24 ). Data from Southern Europe highlighted a higher prevalence; adolescent hypertension was estimated to be at least 9% in Turkey to 13% in Portugal ( 25 - 27 ).…”
Section: Discussionmentioning
confidence: 99%